Structural characterization and macrophage immunostimulatory activity of polysaccharides present in the hot water extracts from Pterospartum tridentatum dried inflorescences - Martins, Vitor Manuel Ramalheira (2018)
The hot water extracts (HWE) from Pterospatum tridentatum dried inflorescences are used in the northeastern portuguese region of Trás-os-Montes due to its therapeutic properties, namely against rheumatism, bladder, liver and kidney disorders [1]. The therapeutic properties attributed to hot water extracts from plants are often related with polysaccharide macrophage immunostimulatory activity [2].